Magnetic nano-ordering in polycrystal and monocrystal chromium - Rozouvan, T.; Yurgelevich, I.; Rozouvan, S.; Poperenko, L. (Functional Materials, 2014)
Surface structures of polycrystalline and monocrystalline samples of chromium were investigated using the following techniques: magnetic force microscopy, scanning tunneling microscopy, and spectral ellipsometric method. Presence of magnetic nanostructure on the surface of polycrystalline chromium has been explained in terms of spin orientation of the atoms. Also we carried out numerical quantum mechanical calculations of chromium supercell and analyzed the results using experimentally obtained curves of the optical conductivity for chromium single crystal.